Dissolved Nitrogen Speciation and Concentration During Spring Thaw in the Greenland Ice Sheet Dark Zone: Evidence for Microbial Activity - Holland, Alexandra T.; Williamson, Christopher J.; Tedstone, Andrew J.; Anesio, Alexandre M.; Tranter, Martyn (Frontiers in Earth Science, 2022)
This study provides a preliminary dataset on the concentration and speciation of dissolved nitrogen (N) in snow, meltwater and ice during the onset of the ablation season within the Dark Zone of the Greenland Ice Sheet. The decaying, partially leached snow pack near S6 in south-west Greenland produced meltwater with relatively constant nitrate (NO3-) concentrations, approximating the snow pack average (1.1 µM). By contrast, ammonium (NH4+) (0 – ~ 4 µM) and dissolved organic nitrogen (DON) (0 – ~ 3 µM) concentrations were more variable, with average snow pack concentrations of 1.0 and 0.4 µM, respectively. This variability could be the result of microbial uptake and production within the melting snow pack. We observed pooled meltwater at the snow-ice interface that appeared to scavenge DON (~ 1 – 8 µM) and possibly NO3- (~ 1 – 2 µM) from the underlying ice, whose initial surface was likely a continuum of superimposed ice and weathering crust from the previous season. The shallow meteoric ice (~10 cm – 1 m) beneath the snow pack had high concentrations of DON and NH4+(6.5 and 2.6 µM, respectively), while NO3- concentrations were similar to the snow pack (1.1 µM). The absence of NH4+ in the snowmelt traversing the snow-ice interface may also point to microbial activity occurring at this boundary layer. Melt modelling indicated the presence of liquid meltwater at the snow-ice interface and that at least 10 cm of the surface ice below the snow pack was at 0 C. Solar radiation transmitted through the thin snow pack to the ice surface is absorbed by pigmented glacier algae to melt the surrounding ice and possibly begin photosynthesis under the thinning snowpack in these micro-melt environments. Hence, we conjecture that glacier algal blooms can commence before the snow pack has completely melted and occur at a time when meltwaters are enhanced in nutrients scavenged from the snowpack, superimposed ice and the remnants of the weathering crust from the previous year.